(untitled) (Andamios, Revista de Investigación Social, 2012)
In order to think reality, we search before the kantian subjective turn: Descartes. Though this may seem strange (Descartes, the father of subjectivity!), we do it because he indeed tries to think reality as such, even though he turns his sight towards subjectivity. After he has found the subjective certainty, a methodic movement, he takes up again the metaphysical questions. Nevertheless, this way keeps frustrated because of the way in wich Descartes concieves the self, so we indagate the Meditations to attend the birth of this concept and glimpse other ressonances, that push toward the non subjective reality, withouth loosing the concept we alredy gained. By doing this, we point to the self as an ungrounded extatic activity.